1970
DOI: 10.1172/jci106312
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dialysates and ultrafiltrates of plasma of saline-loaded dogs on toad bladder sodium transport

Abstract: A B S T R A C T In order to obtain direct evidence for the existence of a natriuretic hormone, dialysates and ultrafiltrates of plasma of dogs expanded with saline were tested for effects on sodium transport by the toad urinary bladder. Dialysate was obtained by dialysis of blood in vivo in a clinical dialyzer and by dialysis in vitro of small volumes of blood using a miniature model of the clinical dialyzer. Ultrafiltrates were prepared using selective molecular filters which permit passage of substances on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

1971
1971
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 28 publications
4
60
0
Order By: Relevance
“…In several studies (8,13,14), the natriuresis paralleled an increase in renal blood flow and glomerular filtration rate suggesting that the factor promoted a natriuresis through a vasodilating effect on the kidney. However, this conclusion is difficult to reconcile with those studies purporting to show a direct effect of this factor on sodium transport in isolated membranes (2,3,5) or tubule fragments (4,7).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In several studies (8,13,14), the natriuresis paralleled an increase in renal blood flow and glomerular filtration rate suggesting that the factor promoted a natriuresis through a vasodilating effect on the kidney. However, this conclusion is difficult to reconcile with those studies purporting to show a direct effect of this factor on sodium transport in isolated membranes (2,3,5) or tubule fragments (4,7).…”
Section: Introductionmentioning
confidence: 73%
“…laboratories (1)(2)(3)(4)(5)(6)(7) have reported the presence of a factor in blood or urine which exhibits natriuretic activity when tested in various biological assay systems, it remains to be established that this factor plays a physiologic role in regulating sodium excretion in the intact animal.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, and most critically, the presence of the inhibitor in the urine of patients and dogs with chronic uremia and of the present dogs with normal renal function appears to correlate with the dictates of maintaining external sodium balance. A number of other investigators have now demonstrated the presence of natriuretic factor(s) or inhibitor(s) of sodium transport in the blood of animals and man using whole animal experiments (13)(14)(15)(16)(17)(18)(19)(20)(21) or in vitro assays (13,18,20,(22)(23)(24)(25)(26)(27)(28)(29). Similarly, extracts of urine have also been shown to contain natriuretic substance(s) (16,17,19,20,(30)(31)(32)(33)(34)(35)(36) or inhibitor(s) of sodium transport (20,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Physiologic studies provided considerable evidence for existence of such a "third factor" capable of modulating urinary sodium excretion independently of filtered sodium load and mineralocorticoid activity (2)(3)(4). Assays in vitro of plasma and urine extracts from subjects and animals with expanded extracellular fluid volume (5,6), certain chronic uremic patients (7), and animals in mineralocorticoid "escape" (8) confirmed the biological effect of sodium transport inhibition across living cell membranes. Several investigators (9)(10)(11) have provided experimental evidence supporting the view that the brain is the source of the natriuretic factor(s).…”
mentioning
confidence: 93%